The Effect of Tillage Systems and Weed Control Methods on Grain Yield and Gluten Protein Compositional and Content-Related Changes in Hybrid Bread Wheat - Jan Buczek (Agriculture, 2024)
The use of simplified tillage systems and weed control methods using reduced herbicide doses in wheat production technology is one of the basic requirements of sustainable agriculture in terms of obtaining high-quality grain of this species. The aim of three-year field studies was to determine the yield and quality characteristics of hybrid wheat grain depending on two tillage systems (CT and RT) and four weed control methods: mechanical (M) and mechanical–chemical, using recommended herbicide doses (MH100) and doses reduced by 25 and 50% (MH75, MH50). A comparable grain yield, number of grains per spike, weight of one thousand wheat grains, and amount of gluten and ω gliadin subunits (GLI) were obtained in the RT and CT systems. The CT system increased protein content (by 15.2 g kg−1) and the increase in the sum of gluten protein fractions was higher for glutenins (GLU) and their LMW and HMW subunits (from 20.9 to 29.8%). The application of the method with the recommended herbicide dose (MH100), compared to M and MH50, resulted in an increase in grain yield by 0.89 and 1.04 t ha−1, respectively, as well as in the sum of GLI (by 8.4 and 12.3%) and GLU (by 13.7 and 25.3%). The application of the herbicide dose reduced by 25% (MH75) compared to the recommended dose (MH100), especially in the RT system, did not cause a significant decrease in protein content and the amount of GLI and GLU, while reducing grain yield (by 0.26 t ha−1) and the amount of gluten (by 3.1%).